2008
DOI: 10.1007/s10144-007-0071-3
|View full text |Cite
|
Sign up to set email alerts
|

Developmental responses to UV‐B radiation in common frogRana temporariaembryos from along an altitudinal gradient

Abstract: Solar ultraviolet radiation (UV) is harmful for developing amphibians. As UV increases with altitude and latitude, it is suggested that high altitude and latitude populations have evolved tolerance to high levels of UV.Using laboratory experiments, we tested the hypothesis that Rana temporaria populations from several altitudes (438-2,450 m above sea level) were adapted to UV by assessing the effects of artificial UV on embryos mortality rate, malformations, and body length at hatching. We also tested the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…The same rationale applies when interpreting biological results from model organisms under a phylogeographic framework. Because of its abundance and broad ecological niche, its wide geographic and altitudinal distribution, as well as its high genomic and phenotypic plasticity, the common frog has been a model system to address fundamental topics in ecological, evolutionary, and conservation sciences, e.g., local adaptation (e.g., Muir, Biek, Thomas, & Mable, ), dispersal (e.g., Dolmen & Seland, ; Palo et al, ), epidemiology (e.g., Duffus, Garner, Nichols, Standridge, & Earl, ), resistance to abiotic stresses (e.g., Marquis, Miaud, & Lena, ), sex determination mechanisms (e.g., Rodrigues, Vuille, Brelsford, Merilä, & Perrin, ), or sex‐chromosome evolution (e.g., Rodrigues, Studer, Dufresnes, & Perrin, ). The present survey thus provides the necessary context to carry out more comprehensive studies on Iberian common frogs, where the overlooked diversity offers a promising playground for future research.…”
Section: Discussionmentioning
confidence: 99%
“…The same rationale applies when interpreting biological results from model organisms under a phylogeographic framework. Because of its abundance and broad ecological niche, its wide geographic and altitudinal distribution, as well as its high genomic and phenotypic plasticity, the common frog has been a model system to address fundamental topics in ecological, evolutionary, and conservation sciences, e.g., local adaptation (e.g., Muir, Biek, Thomas, & Mable, ), dispersal (e.g., Dolmen & Seland, ; Palo et al, ), epidemiology (e.g., Duffus, Garner, Nichols, Standridge, & Earl, ), resistance to abiotic stresses (e.g., Marquis, Miaud, & Lena, ), sex determination mechanisms (e.g., Rodrigues, Vuille, Brelsford, Merilä, & Perrin, ), or sex‐chromosome evolution (e.g., Rodrigues, Studer, Dufresnes, & Perrin, ). The present survey thus provides the necessary context to carry out more comprehensive studies on Iberian common frogs, where the overlooked diversity offers a promising playground for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet radiation is widely mentioned as a damaging environmental factor for organisms in both terrestrial and aquatic systems (33,34). The effects derived from a deleterious UV exposure are known to cause irreparable effects at different levels from organism survival and reproduction (8–11) to cellular metabolism and viability (13,14). However, the molecular responses triggered in an animal organism after a UV exposure are not yet understood.…”
Section: Discussionmentioning
confidence: 99%
“…The significant level was P < 0.05. UV exposure are known to cause irreparable effects at different levels from organism survival and reproduction (8)(9)(10)(11) to cellular metabolism and viability (13,14). However, the molecular responses triggered in an animal organism after a UV exposure are not yet understood.…”
Section: Discussionmentioning
confidence: 99%
“…Perotti and Diéguez [92] also found that the optical properties of the egg jelly envelope surrounding the embryo is also correlated with embryonic melanin concentration: the egg jelly of the species with the lowest embryonic melanin concentration (P. thaul) had the highest UVR absorbance whereas the egg jelly of the species with the highest embryonic melanin concentration (R. spinulosa) had the lowest UVR absorbance. Several additional studies have similarly shown that the UVR absorbance by the egg jelly envelope varies with wavelength and among species [93][94][95][96][97], and also the protective role of the jelly envelope varies among populations within a species along an elevation gradient [98]. Such research indicates that for some species the jelly envelope may provide adequate protection against UVR for the embryo, whereas others may rely on alternative defence strategies such as pigmentation, behavioural avoidance (e.g.…”
Section: Uvr-screening Compounds and Egg Jellymentioning
confidence: 96%